The Reasons of Young Consumers' Choice on Chain Café Stores: A Research on Starbucks - Akgün, Serkan; Yalım, Funda (International Review of Management and Marketing, 2015)
Corporations providing services and making goods are forced to ensure customer satisfaction, to build brand loyalty, to change the way being in service by taking some changes into consideration, such as changes in living conditions, in consumers' supply and demand, fierce competition environment. At this point, chain café stores are appeared as preferred ones by especially young consumers in direct proportion to changes in consumers' supply and demand. Young consumers, while going for a chain café store, pay regard to several criteria, such as store image, store atmosphere, goods/services specifications, and price policies. This study aims to measure the effect of young consumers going for Starbucks chain café stores on customer loyalty. This research, according to the analysis of surveys taken by 187 persons, reveals that brand image and brand follow-up have an effect on brand loyalty. Keywords: Brand; consumer behaviors; chain café store brands JEL Classifications: M